Understanding the Structure, Thermal, Pasting, and Rheological Properties of Potato and Pea Starches Affected by Annealing Using Plasma-Activated Water - Yan, Yizhe; Peng, Baixiang; Niu, Bin; Ji, Xiaolong; He, Yuan; Shi, Miaomiao (Frontiers in Nutrition, 2022)
In this research, annealing (ANN) using plasma-activated water (PAW) was first employed to modify potato and pea starches. Compared with the conventional ANN using distilled water (DW), the granular morphology of two starches was not significantly affected by PAW-ANN. The results of X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy showed that PAW-ANN could reduce the long and short-range ordered structure of potato starch while improving the long and short-range ordered structure of pea starch. Differential scanning calorimetry (DSC) analysis indicated that PAW-ANN lowered the gelatinization enthalpy of potato starch and increased the gelatinization enthalpy of pea starch. The analysis of viscosity and dynamic rheological characteristics illustrated that PAW-ANN reduced the peak viscosity and improved the gel strength of starch pastes. PAW-ANN represents a novel modification method for modifying the structure, reducing the viscosity, improving the gel strength of starch, and is very promising for applying in starch-based hydrogels and food additives.